Band structure engineering in highly degenerate tetrahedrites through isovalent doping. Issue 43 (20th October 2016) - Lu, Xu; Yao, Wei; Wang, Guiwen; Zhou, Xiaoyuan; Morelli, Donald; Zhang, Yongsheng; Chi, Hang; Hui, Si; Uher, Ctirad
Abstract : It can be difficult to reduce the electrical resistivity of highly degenerate semiconductors due to their high carrier concentration, impeding the further increase in their thermoelectric power factor. Abstract : It can be difficult to reduce the electrical resistivity of highly degenerate semiconductors due to their high carrier concentration, impeding the further increase in their thermoelectric power factor. Here we report on an enhancement in the power factor of highly degenerate Cu12 Sb4 S13− x Se x solid solutions, which show a dramatic decrease in the electrical resistivity while maintaining a constant Seebeck coefficient for various contents of Se. Rather than arising from an increased carrier concentration, the reduced electrical resistivity is a consequence of the upward displacement of the valence bands with low effective masses. Using theoretical calculations, we show that these additional valence bands have a similar density of states effective mass to that of the existing conduction valley, thus yielding unchanged Seebeck coefficients. The results suggest that the power factor of highly degenerate semiconductors can be enhanced through careful band structure engineering via isovalent doping.